The Effect of Augmented Reality Learning Media on Motivation and Social Studies Learning Outcomes in Elementary Schools: Pengaruh Media Pembelajaran Augmented Reality Terhadap Motivasi dan Hasil Belajar IPS Sekolah Dasar - Dewoto Kusumo; Rifki Afandi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of augmented reality learning media on students' motivation and learning outcomes in elementary social studies subjects. The research method used is quantitative experimental, pre experimental design, one group pretest-posttest. The data collection technique was done by giving pretest and posttest. Data analysis techniques using inferential statistics include parametric statistics using paired sample t-test. The results of the study found that there was a big influence on the use of augmented reality learning media on students' motivation and learning outcomes in elementary social studies subjects. There are two aspects of increasing students' learning motivation including intrinsic and extrinsic aspects. Meanwhile, the increase in student learning outcomes in the cognitive domain is at levels C1, C2 and C3. The results of this study suggest that teachers, especially teachers at the elementary level, make more use of technology in making learning media, especially in social studies subjects. In addition to facilitating the planting of learning concepts, the use of technology-based learning media is also useful in making learning activities more interesting and making it easier for students to understand learning materials.